2017
DOI: 10.1038/s41598-017-15697-8
|View full text |Cite
|
Sign up to set email alerts
|

Specific Light-Up System for Protein and Metabolite Targets Triggered by Initiation Complex Formation

Abstract: Gene regulation systems are mimicked by simple quantitative detection of non-nucleic acid molecular targets such as protein and metabolite. Here, we describe a one-tube, one-step real-time quantitative detection methodology for isothermal signal amplification of those targets. Using this system, real-time quantitative detection of thrombin and streptomycin, which were used as examples for protein and metabolite targets, was successfully demonstrated with detection limits of at most 50 pM and 75 nM, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…We then demonstrated that ThT-HE binds to parallel G4 in particular and exhibits strong fluorescence while maintaining the low background emission properties of ThT [17]. In addition, we reported the application of ThT-HE to G4 detection systems [18][19][20]. Since then, ThT with an ethyl group introduced at the N 3 -position (ThT-E) has been reported by Guan et al [21], but the derivatization of ThT at the N 3 -position has not seen significant progress otherwise.…”
Section: Fluorescence Spectral Analysis Of Tht Tht-he and Tht-aementioning
confidence: 86%
“…We then demonstrated that ThT-HE binds to parallel G4 in particular and exhibits strong fluorescence while maintaining the low background emission properties of ThT [17]. In addition, we reported the application of ThT-HE to G4 detection systems [18][19][20]. Since then, ThT with an ethyl group introduced at the N 3 -position (ThT-E) has been reported by Guan et al [21], but the derivatization of ThT at the N 3 -position has not seen significant progress otherwise.…”
Section: Fluorescence Spectral Analysis Of Tht Tht-he and Tht-aementioning
confidence: 86%
“…Previously, we developed ThT derivatives by introducing substituents instead of methyl groups at the N 3 position adjacent to the rotational axis . We demonstrated that these fluorophores enabled the selective emission of fluorescence upon binding to parallel G4s. However, so far, targets of ThT are still limited to β-sheet-rich proteins like amyloid fibrils and some nucleic acid structures mentioned above. Accordingly, in this study, we attempted to develop a fluorescence probe having a target-directing property that is different from that of the unmodified ThT in the conjugation of a ligand to the N 3 position.…”
mentioning
confidence: 99%